Non-homologous DNA end joining and alternative pathways to double-strand break repair - Chang, Howard H. Y. (Nat Rev Mol Cell Biol, 2017)
DNA double-strand breaks (DSBs) are the most dangerous type of DNA damage because they can result in the loss of large chromosomal regions. In all mammalian cells, DSBs that occur throughout the cell cycle are repaired predominantly by the non-homologous DNA end joining (NHEJ) pathway. Defects in NHEJ result in sensitivity to ionizing radiation and the ablation of lymphocytes. The NHEJ pathway utilizes proteins that recognize, resect, polymerize and ligate the DNA ends in a flexible manner. This flexibility permits NHEJ to function on a wide range of DNA-end configurations, with the resulting repaired DNA junctions often containing mutations. In this Review, we discuss the most recent findings regarding the relative involvement of the different NHEJ proteins in the repair of various DNA-end configurations. We also discuss the shunting of DNA-end repair to the auxiliary pathways of alternative end joining (a-EJ) or single-strand annealing (SSA) and the relevance of these different pathways to human disease.